The evolution of computer use in human resource management: Interviews with ten leaders - Broderick, Renae; Boudreau, John W. (Human Resource Management, 1991)
AbstractUsing an exploratory model of the evolution of computers systems in organizations, the authors interviewed HR computer systems people in ten Fortune 500 firms considered leaders in HR computer use. Generalizable measures of growth in computer use and related changes in HR department structure, strategy, and personnel were found. These measures were used to identify three stages of growth in computer use: threshold, growth, and consolidation/strategic expansion. In the latter two stages, differences were found among firms in the way computer use evolved. These differences appeared closely related to the company's choice of technology and the centralization of the firm's key HR decision makers. The implications of the exploratory model and findings for practice and future research are discussed.